Composite coated soft magnetic material and preparation method and application thereof

Through the composite coating method, the alloy powder is first coated with a silicone resin layer, and then the metal salt is adsorbed through chemical precipitation. This solves the problem that the existing soft magnetic powder core is difficult to achieve both high magnetic permeability and low loss, and achieves soft magnetic Uniform coating of materials and high performance magnetic powder core preparation.

CN119361315APending Publication Date: 2025-01-24HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411654251.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing soft magnetic powder cores are difficult to have high magnetic permeability and low loss, and have poor insulation coating effect.

Method used

Using the composite coating method, the alloy powder is first coated with a silicone resin layer, and then the metal salt is adsorbed on the silicone resin layer through chemical precipitation to form a uniform metal oxide coating layer. The coupling agent improves the adsorption effect of the coating agent.

Benefits of technology

The uniform covering of soft magnetic materials is realized, the insulation effect and resistance are improved, the loss is reduced, and the performance of high magnetic guidance and high frequency and low loss is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141746950000111
    Figure BDA0005141746950000111
  • Figure BDA0005141746950000121
    Figure BDA0005141746950000121
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of soft magnetic materials, and particularly relates to a composite coated soft magnetic material and a preparation method and application thereof. The preparation method comprises the following steps: (1) preparing an organic silicon resin coated alloy from alloy powder and organic silicon resin; (2) preparing a solution containing metal salt; adding the organic silicon resin coated alloy into the solution containing the metal salt to obtain dispersion liquid; an alkaline compound is added into the dispersion liquid, and magnetic powder is obtained after primary annealing; and (3) mixing the magnetic powder, an adsorbent, a cross-linking agent and a first auxiliary agent, granulating, pressing, and carrying out secondary annealing. The coating layer of the soft magnetic material prepared by the preparation method is uniform in coating and has a relatively good insulation effect; the resistivity can be improved, so that the purpose of reducing the loss is achieved, and excellent performances such as high magnetic conductivity and low loss under high frequency can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic material preparation, and specifically relates to a composite coated soft magnetic material and a preparation method and application thereof. Background Art

[0002] Metal soft magnetic powder core is a kind of metal composite material mainly composed of ferromagnetic powder, which is pressed after being coated with insulating medium. It has the advantages of high operating frequency, wide frequency application range, excellent soft magnetic properties, and low cost. It can meet the current application requirements of high frequency, high DC superposition effect, large current and high power density of electronic components. Soft magnetic alloy powder is the main material for the preparation of magnetic powder cores and integrated inductors. It has performance advantages such as high magnetic permeability, low high-frequency loss, and high saturation magnetic induction intensity. In production, it can be pressed into components of different shapes according to actual needs. At the same time, magnetic powder cores have been widely used in electronic products, home appliances, new energy, 5G communications, photovoltaic power generation and other fields.

[0003] At present, the research on improving the performance of magnetic powder core materials is mainly focused on the insulation coating process, which is the key to obtaining low-loss materials and one of the important factors affecting the frequency of material use. The traditional insulation coating process mainly uses a direct mixing method to coat a layer of insulating material on the surface of the powder. According to the characteristics of the coating material, it is divided into organic insulation coating and inorganic coating, such as phosphoric acid passivation coating or inorganic oxide direct coating. Organic insulation coating is not resistant to high temperatures and can only be subjected to low-temperature heat treatment. It is impossible to eliminate the residual stress after pressing and molding, and the magnetic properties are relatively low. Although inorganic coated powders have good heat resistance, the powders cannot be evenly coated, and the thermal expansion coefficients between oxide powders and alloy powders do not match. During pressing or at high temperatures, the coating layer will fall off, resulting in a decrease in resistivity, which in turn leads to worsening losses.

[0004] At present, there are many studies and reports on the insulation coating of soft magnetic powder. For example, the prior art discloses a method for preparing a metal soft magnetic powder core, which first performs organic insulation coating and then uses a silane coupling agent for modification coupling. Although this method can obtain a soft magnetic powder core with excellent DC bias performance and low high-frequency loss, it cannot achieve the effect of uniform coating on the surface of the magnetic powder. The particles are easy to agglomerate, the porosity of the magnetic core is large, and the magnetic permeability is low, which cannot meet the effect of high magnetic permeability and low loss. The prior art also discloses a soft magnetic alloy powder with an insulating layer coating soft magnetic metal powder particles, the insulating layer includes a metal salt layer composed of iron and iron oxide and a phosphate glass layer. This coating method is prone to agglomeration, and the insulating layer cannot be evenly coated on the powder surface. In addition, since iron has the characteristic of low resistance, it is easy to reduce the resistivity of the powder, thereby increasing the powder loss and causing the magnetic properties to deteriorate. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that the soft magnetic powder core is difficult to have both high magnetic permeability and low loss, and the insulation coating effect is poor, thereby providing a composite coated soft magnetic material and its preparation method and application.

[0006] To this end, the present invention provides the following technical solutions.

[0007] The present invention provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0008] (1) preparing an organic silicon resin coated alloy by combining alloy powder and organic silicon resin; the mass ratio of the alloy powder to the organic silicon resin is 100:(0.2-0.8);

[0009] (2) preparing a solution containing a metal salt; adding the silicone resin coated alloy to the solution containing the metal salt to obtain a dispersion; adding an alkaline compound to the dispersion, and performing a single annealing to obtain magnetic powder; wherein the metal salt comprises at least one of a metal chloride and ammonium molybdate;

[0010] (3) The magnetic powder, adsorbent, cross-linking agent and first auxiliary agent are mixed and granulated, pressed and subjected to secondary annealing; wherein the adsorbent comprises ammonium phosphomolybdate, and the cross-linking agent comprises calcium alginate.

[0011] The present invention first coats the alloy with a silicone resin layer to ensure insulation and prevent the magnetic properties from decreasing due to oxidation, and then adsorbs the metal salt on the silicone resin layer on the surface of the alloy powder again by chemical precipitation to form a secondary coating, and forms a uniform metal oxide coating layer after secondary annealing, and improves the adsorption effect of the coating agent on the powder surface by adding an adsorbent and a cross-linking agent, thereby improving the insulation effect of the powder. The present invention utilizes the hydrophobicity of the silicone resin, and the metal salt formed by chemical precipitation is attached to the resin surface to improve the coating uniformity, which helps to improve the resistivity and thus reduce the loss. At the same time, the magnetic powder core obtained by the method also has the characteristics of high body density, less internal odor, high magnetic permeability, high frequency and low loss, etc., has good mechanical strength, simple and easy process flow, and low requirements for production equipment.

[0012] In an optional embodiment, in the step (2), the mass ratio of the silicone resin coated alloy to the metal salt is 100:(0.5-2); as an example, the mass ratio of the silicone resin coated alloy to the metal salt is 100:0.5, 100:0.8, 100:1.2, 100:1.5, 100:2 or a ratio within a range consisting of any two ratios.

[0013] Preferably, the metal chloride includes at least one of magnesium chloride, aluminum chloride, zinc chloride, bismuth chloride, manganese chloride, zirconium tetrachloride and calcium chloride.

[0014] In an optional embodiment, the alkaline compound is at least one of sodium hydroxide, potassium hydroxide and ammonia water;

[0015] Preferably, an alkaline compound is added to adjust the pH of the dispersion to 7.5-8.

[0016] In an optional embodiment, in step (1), the alloy powder is at least one of FeSi, FeNi, FeSiAl, FeNiMo and FeSiCr;

[0017] Preferably, the mesh size of the alloy powder is 200 to 1000 mesh;

[0018] Preferably, the mesh size of the silicone resin coated alloy is 100 to 200 meshes.

[0019] In an optional embodiment, the step (1), when preparing the organic silicon resin coated alloy, further comprises the step of adding a solvent;

[0020] Preferably, the mass ratio of the silicone resin to the solvent is (0.2-0.8):10;

[0021] Preferably, the solvent is at least one of acetone and ethanol.

[0022] The step (1) specifically comprises: mixing alloy powder, silicone resin and solvent, drying and screening, wherein the drying temperature is 80-160°C.

[0023] In an optional embodiment, the step (2), the primary annealing step comprises heating to 450°C to 600°C at a heating rate of 1 to 2°C / min and maintaining the temperature for 0.5 to 12 hours;

[0024] Preferably, the primary annealing is performed under a protective atmosphere, such as argon, nitrogen, or a mixture of nitrogen and argon.

[0025] In an optional embodiment, in the step (3), preferably, the amount of the adsorbent is 0.5 to 3 wt % of the magnetic powder;

[0026] Preferably, the amount of the adsorbent is 0.5 to 2 wt % of the magnetic powder;

[0027] Preferably, the amount of the cross-linking agent is 0.2-1 wt% of the magnetic powder;

[0028] Preferably, the first auxiliary agent includes an adhesive;

[0029] Preferably, the step of adding a release agent is further included after the granulation;

[0030] Preferably, the amount of the adhesive is 1.5 to 3 wt % of the magnetic powder;

[0031] Preferably, the amount of the release agent is 0.3-3 wt % of the magnetic powder;

[0032] Preferably, the adhesive is at least one of epoxy resin, silicone resin and phenolic resin;

[0033] Preferably, the release agent is at least one of zinc stearate, barium stearate, aluminum stearate, talc, and boron nitride.

[0034] In an optional embodiment, in step (3), the pressing pressure is 10 to 20 T / cm 2 , time is 0.5~30s;

[0035] Preferably, the secondary annealing step comprises heating to 450-850°C at a heating rate of 1.5-3°C / min and keeping the temperature for 1-3h;

[0036] Preferably, the temperature of the secondary annealing is 500-850°C;

[0037] Preferably, the secondary annealing is performed in a nitrogen atmosphere.

[0038] The invention also provides a composite coated soft magnetic material obtained by the above preparation method.

[0039] The present invention also provides an application of the composite coated soft magnetic material obtained by the preparation method as a magnetic powder core or in an inductor device.

[0040] The technical solution of the present invention has the following advantages:

[0041] 1. The preparation method of the composite coated soft magnetic material provided by the present invention comprises: (1) preparing an alloy powder and an organic silicon resin into an organic silicon resin coated alloy; (2) preparing a solution containing a metal salt; adding the organic silicon resin coated alloy into the solution containing the metal salt to obtain a dispersion; adding an alkaline compound into the dispersion, and obtaining magnetic powder after a primary annealing; (3) mixing and granulating the magnetic powder, adsorbent, cross-linking agent and first auxiliary agent, pressing and secondary annealing. The coating layer of the soft magnetic material obtained by the preparation method is uniformly coated and has a good insulation effect; it is helpful to improve the resistivity and thus achieve the purpose of reducing the loss, and can take into account the excellent properties such as high magnetic permeability and low loss at high frequency. The present invention first coats the alloy with a silicone resin layer to ensure insulation and prevent the magnetic properties from decreasing due to oxidation, and then adsorbs the metal salt on the silicone resin layer on the surface of the alloy powder again by chemical precipitation to form a secondary coating, and forms a uniform metal oxide coating layer after secondary annealing, and improves the adsorption effect of the coating agent on the powder surface by adding an adsorbent and a cross-linking agent, thereby improving the insulation effect of the powder. The present invention utilizes the hydrophobicity of the silicone resin, and the metal salt formed by chemical precipitation is attached to the resin surface to improve the coating uniformity, which helps to improve the resistivity and thus reduce the loss. At the same time, the magnetic powder core obtained by the method also has the characteristics of high body density, less internal odor, high magnetic permeability, high frequency and low loss, etc., has good mechanical strength, simple and easy process flow, and low requirements for production equipment.

[0042] 2. The preparation method of the composite coated soft magnetic material provided by the present invention selects a specific metal salt, such as at least one of magnesium chloride, aluminum chloride, zinc chloride, bismuth chloride, manganese chloride, zirconium tetrachloride, calcium chloride and ammonium molybdate, etc., which can further improve the resistivity of the powder and reduce the loss. The present invention uses metal chloride, and the obtained dispersion has better dispersibility, so that the coating material can be evenly coated on the surface of the powder. DETAILED DESCRIPTION

[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0045] Example 1

[0046] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0047] (1) According to weight, 100 g of sendust powder (mesh size is 300 mesh), 0.2 g of silicone resin and 10 g of acetone were weighed and mixed evenly, dried at 120° C. and passed through a 200 mesh sieve to obtain a silicone resin coated alloy. The silicone resin model is SH-9602, and the manufacturer is Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.

[0048] (2) Weigh 1 g of magnesium chloride and dissolve it in 50 g of deionized water, add 100 g of the silicone resin-coated alloy obtained in step (1), and stir to obtain a dispersion; add a NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat the washing twice, dry, pass through a 100-mesh sieve, and anneal once in nitrogen at a heating rate of 1° C. / min, an annealing temperature of 550° C., and a time of 1 h to obtain magnetic powder.

[0049] (3) Based on the mass of the magnetic powder, add 2wt% epoxy resin and mix, then add 0.5wt% ammonium phosphomolybdate and 0.2wt% calcium alginate, mix evenly, dry, and sieve to granulate. Add 0.35wt% of the release agent zinc stearate to the processed magnetic powder and mix evenly; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0050] Example 2

[0051] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0052] (1) Weigh 100 g of sendust powder (mesh size: 300 mesh), 0.2 g of silicone resin and 10 g of acetone according to weight, stir and mix evenly, dry at 120° C. and pass through a 200 mesh sieve to obtain a silicone resin coated alloy.

[0053] (2) 1.8 g of magnesium chloride was dissolved in 50 g of deionized water, and 100 g of the silicone resin-coated alloy obtained in step (1) was added, and the mixture was stirred to obtain a dispersion; an aqueous NaOH solution was added dropwise to the dispersion until the pH value was greater than 7.5, and the dispersion was stirred for 10 min and then vacuum filtered. The dispersion was washed twice, dried, passed through a 100-mesh sieve, and annealed once in nitrogen at a temperature of 580° C., a heating rate of 1.5° C. / min, and an annealing time of 1 h to obtain magnetic powder.

[0054] (3) Based on the mass of the magnetic powder, add 2wt% epoxy resin and mix, then add 0.6wt% ammonium phosphomolybdate and 0.4wt% calcium alginate, mix evenly, dry, and sieve to granulate. Add 0.35wt% of the release agent zinc stearate to the treated magnetic powder and mix evenly; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0055] Example 3

[0056] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0057] (1) 100 g of sendust powder (mesh size: 300 mesh), 0.2 g of silicone resin and 10 g of acetone were mixed uniformly according to weight proportions, and dried at 120° C. and passed through a 200 mesh sieve to obtain a silicone resin coated alloy.

[0058] (2) Weigh 0.6 g of magnesium chloride and dissolve it in 50 g of deionized water, add 100 g of the silicone resin-coated alloy obtained in step (1), and stir continuously to obtain a dispersion; add a NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat the washing twice, dry through a 100-mesh sieve, and anneal once in nitrogen at a temperature of 585° C., a heating rate of 1.5° C. / min, and a time of 1 h to obtain magnetic powder.

[0059] (3) Based on the mass of magnetic powder, add 2wt% epoxy resin, then add 0.8wt% ammonium phosphomolybdate and 0.5wt% calcium alginate, mix well, dry, and sieve to granulate. Add 0.35wt% of release agent zinc stearate to the processed magnetic powder and mix well; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0060] Example 4

[0061] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0062] (1) Weigh 100 g of sendust (300 mesh), 0.5 g of silicone resin and 10 g of acetone according to weight, stir and mix them evenly, and dry them at 120° C. through a 200 mesh sieve to obtain a silicone resin coated alloy.

[0063] (2) Weigh 1 g of magnesium chloride and dissolve it in 50 g of deionized water, add 100 g of the silicone resin-coated alloy obtained in step (1), and stir continuously to obtain a dispersion. Add a NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat the washing twice, dry through a 100-mesh sieve, and anneal once in nitrogen at a temperature of 585° C., a heating rate of 1.5° C. / min, and an annealing time of 1 h to obtain magnetic powder.

[0064] (3) Based on the mass of the magnetic powder, add 2wt% epoxy resin, then add 1.2wt% ammonium phosphomolybdate and 0.6wt% calcium alginate, mix well, dry, and sieve to granulate. Add 0.35wt% of the release agent zinc stearate to the treated magnetic powder and mix well; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0065] Example 5

[0066] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0067] (1) Weigh 100 g of sendust powder (mesh size: 300 mesh), 0.8 g of silicone resin and 10 g of acetone by weight, stir and mix them evenly, and dry them at 120° C. through a 200 mesh sieve to obtain a silicone resin-coated alloy.

[0068] (2) Weigh 1 g of magnesium chloride and dissolve it in 50 g of deionized water, add 100 g of the silicone resin-coated alloy treated in step (1), and stir continuously to obtain a dispersion; add a NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat the washing twice, dry through a 100-mesh sieve, and anneal once in nitrogen at a temperature of 600° C., a heating rate of 1.8° C. / min, and a time of 1 h to obtain magnetic powder.

[0069] (3) Based on the mass of magnetic powder, add 2wt% epoxy resin, then add 1.6wt% ammonium phosphomolybdate and 0.5wt% calcium alginate, mix well, dry, and sieve to granulate. Add 0.35wt% of release agent zinc stearate to the treated magnetic powder and mix well; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0070] Example 6

[0071] This embodiment provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0072] (1) According to weight, 100 g of iron-nickel powder (mesh size is 300 mesh), 0.2 g of silicone resin and 10 g of ethanol were weighed and mixed evenly, dried at 120° C. and passed through a 200 mesh sieve to obtain a silicone resin coated alloy. The silicone model is sh-9501, and the manufacturer is Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.

[0073] (2) Weigh 2 g of zinc chloride and dissolve it in 50 g of deionized water, add 100 g of the silicone resin-coated alloy obtained in step (1), and stir to obtain a dispersion; add a NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat the washing twice, dry, pass through a 100-mesh sieve, and anneal once in nitrogen at a heating rate of 1° C. / min, a temperature of 480° C., and a time of 8 h to obtain magnetic powder.

[0074] (3) Based on the mass of the magnetic powder, add 2.5wt% phenolic resin and mix, then add 0.5wt% ammonium phosphomolybdate and 0.2wt% calcium alginate, mix evenly, dry, and sieve to granulate. Add 1.0wt% of release agent boron nitride to the treated magnetic powder and mix evenly; 2 The magnetic ring was pressed into a magnetic ring with a pressure of 20s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 1.8℃ / min, the temperature was raised to 680℃, and the temperature was kept for 2h.

[0075] Example 7

[0076] This embodiment provides a method for preparing a composite coated soft magnetic material, which differs from Embodiment 1 in that aluminum chloride is used instead of magnesium chloride.

[0077] Example 8

[0078] This embodiment provides a method for preparing a composite coated soft magnetic material, which differs from Embodiment 1 in that ammonium molybdate is used instead of magnesium chloride.

[0079] Example 9

[0080] This embodiment provides a method for preparing a composite coated soft magnetic material, which differs from Embodiment 1 in that bismuth chloride is used instead of magnesium chloride.

[0081] Example 10

[0082] This embodiment provides a method for preparing a composite coated soft magnetic material, which is different from Embodiment 1 in that the amount of magnesium chloride added is changed from 1 g to 0.5 g.

[0083] Embodiment 11

[0084] This embodiment provides a method for preparing a composite coated soft magnetic material, which differs from Embodiment 1 in that the temperature of the secondary annealing in step (3) is changed from 600°C to 450°C.

[0085] Comparative Example 1

[0086] This comparative example provides a method for preparing a composite coated soft magnetic material, which is different from Example 1 in that the weight portion of the organic silicon resin in step (1) is 2 g.

[0087] Comparative Example 2

[0088] This comparative example provides a method for preparing a composite coated soft magnetic material, which differs from Example 1 in that the organic silicon is removed in step (1), and comprises the following steps:

[0089] (1) Weigh 1 g of magnesium chloride and dissolve it in 50 g of deionized water, add sendust powder (mesh size is 300 mesh), and stir to obtain a dispersion; add NaOH aqueous solution dropwise to the dispersion until the pH is greater than 7.5, stir for 10 min, and then vacuum filter, repeat washing twice, dry, pass through a 100-mesh sieve, and anneal once in nitrogen at a heating rate of 1°C / min, a temperature of 550°C, and a time of 1 h to obtain magnetic powder.

[0090] (2) Based on the mass of the magnetic powder, add 2wt% epoxy resin and mix, then add 0.5wt% ammonium phosphomolybdate and 0.2wt% calcium alginate, mix evenly, dry, and sieve to granulate. Add 0.35wt% of the release agent zinc stearate to the treated magnetic powder and mix evenly; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0091] Comparative Example 3

[0092] This comparative example provides a method for preparing a composite coated soft magnetic material, comprising the following steps:

[0093] (1) Weigh 100 g of sendust powder (mesh size: 300 mesh), 0.8 g of silicone resin and 10 g of acetone by weight, stir and mix them evenly, and dry them at 120° C. through a 200 mesh sieve to obtain a silicone resin-coated alloy.

[0094] (2) Weigh 1 g of magnesium oxide and 20 g of acetone, add 100 g of the silicone resin-coated alloy treated in step (1), dry through a 100-mesh sieve, and anneal once in nitrogen at a temperature of 600° C., a heating rate of 1.8° C. / min, and a time of 1 h to obtain magnetic powder.

[0095] (3) Based on the mass of magnetic powder, add 2wt% epoxy resin, mix evenly, dry, and sieve to granulate. Add 0.35wt% of release agent zinc stearate to the processed magnetic powder and mix evenly; 2 The magnetic ring was pressed into a magnetic ring with a pressing time of 1s. The magnetic core was obtained by annealing in a nitrogen atmosphere with a heating rate of 2.2℃ / min, the temperature was raised to 600℃, and the temperature was kept for 1h.

[0096] Test example

[0097] This test example provides performance tests of the magnetic cores of various embodiments and comparative examples, as follows:

[0098] Use the instrument SY-8232-BH to test the magnetic permeability and loss of the magnetic core;

[0099] Use a multimeter to test the core resistance.

[0100] Table 1 Performance test results of magnetic core

[0101]

[0102]

[0103] According to the above results, it can be seen that the present invention first coats the alloy with an organic silicon resin layer to ensure insulation and prevent the magnetic properties from decreasing due to oxidation, and then adsorbs the metal salt on the organic silicon resin layer on the surface of the alloy powder by chemical precipitation to form a secondary coating, and under the action of specific adsorbents and cross-linking agents, the adsorption effect is improved, and the insulation effect of the powder is improved. When testing the resistance of the composite coated soft magnetic material, it is OL, indicating that the resistance is high and the insulation effect is good. Combined with the permeability and loss data, the composite coated soft magnetic material prepared by the present invention has the advantages of low loss and high permeability. Combined with Comparative Examples 1-2, the mass ratio of the alloy powder and the organic silicon resin of the present invention is 100: (0.2-0.8), and the organic silicon resin is coated on the alloy, which helps to reduce loss and improve permeability. Combined with Comparative Example 3, the present invention uses chemical precipitation to make the metal salt adhere to the organic silicon resin layer on the surface of the alloy, which can make the composite coated soft magnetic material have the characteristics of high permeability, high frequency and low loss.

[0104] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a composite coated soft magnetic material, characterized in that: The following steps are involved: (1) preparing an organic silicon resin coated alloy by combining alloy powder and organic silicon resin; the mass ratio of the alloy powder to the organic silicon resin is 100:(0.2-0.8); (2) preparing a solution containing a metal salt; adding the silicone resin coated alloy to the solution containing the metal salt to obtain a dispersion; adding an alkaline compound to the dispersion, and performing a single annealing to obtain magnetic powder; wherein the metal salt comprises at least one of a metal chloride and ammonium molybdate; (3) The magnetic powder, adsorbent, cross-linking agent and first auxiliary agent are mixed and granulated, pressed and subjected to secondary annealing; wherein the adsorbent comprises ammonium phosphomolybdate, and the cross-linking agent comprises calcium alginate.

2. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the silicone resin coated alloy to the metal salt is 100:(0.5-2); Preferably, the metal chloride includes at least one of magnesium chloride, aluminum chloride, zinc chloride, bismuth chloride, manganese chloride, zirconium tetrachloride and calcium chloride.

3. The preparation method according to claim 1 or 2, characterized in that: The alkaline compound is at least one of sodium hydroxide, potassium hydroxide and ammonia water; Preferably, an alkaline compound is added to adjust the pH of the dispersion to 7.5-8.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (1), the alloy powder is at least one of FeSi, FeNi, FeSiAl, FeNiMo and FeSiCr; Preferably, the mesh size of the alloy powder is 200 to 1000 mesh; Preferably, the mesh size of the silicone resin coated alloy is 100 to 200 meshes.

5. The preparation method according to claim 4, characterized in that: The step (1), when preparing the organic silicon resin coated alloy, further comprises the step of adding a solvent; Preferably, the mass ratio of the silicone resin to the solvent is (0.2-0.8):10; Preferably, the solvent is at least one of acetone and ethanol.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The step (2), the primary annealing step comprises heating to 450°C to 600°C at a heating rate of 1 to 2°C / min and maintaining the temperature for 0.5 to 12 hours; Preferably, the primary annealing is performed under a protective atmosphere.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (3), preferably, the amount of the adsorbent is 0.5 to 3 wt % of the magnetic powder; Preferably, the amount of the adsorbent is 0.5 to 2 wt % of the magnetic powder; Preferably, the amount of the cross-linking agent is 0.2-1 wt% of the magnetic powder; Preferably, the first auxiliary agent includes an adhesive; Preferably, the step of adding a release agent is further included after the granulation; Preferably, the amount of the adhesive is 1.5 to 3 wt % of the magnetic powder; Preferably, the amount of the release agent is 0.3-3 wt % of the magnetic powder; Preferably, the adhesive is at least one of epoxy resin, silicone resin and phenolic resin; Preferably, the release agent is at least one of zinc stearate, barium stearate, aluminum stearate, talc, and boron nitride.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (3), the pressing pressure is 10 to 20 T / cm 2 , time is 0.5~30s; Preferably, the secondary annealing step comprises heating to 450-850°C at a heating rate of 1.5-3°C / min and keeping the temperature for 1-3h; Preferably, the temperature of the secondary annealing is 500-850°C; Preferably, the secondary annealing is performed in a nitrogen atmosphere.

9. The composite coated soft magnetic material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the composite coated soft magnetic material obtained by the preparation method according to any one of claims 1 to 8 as a magnetic powder core or in an inductor device.